2019
DOI: 10.21608/jssae.2019.43221
|View full text |Cite
|
Sign up to set email alerts
|

Impact of some Organic and Inorganic Amendments on some Soil Properties and Wheat Production under Saline-Sodic Soil

Abstract: Two field experiments were conducted at two sites in Sakha Agric. Res. Station Farm, North Delta, during two successive winter seasons, 2017/2018 and 2018/2019 to study the effect of individual and combined applications of gypsum, compost tea and biochar on some soil properties and wheat (Triticum aestivum, L) productivity under saline and saline-sodic soils. Gypsum requirements (G), 400 L compost tea (C), 1 Mg biochar (B 1) or 2 Mg biochar (B 2) were applied. Data revealed that application of G+ C+ B2 decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
7
12
0
Order By: Relevance
“…So, the effect different treatments on soil bulk density followed the ascending order such as: compost > gypsum > zeolite > magnetite >Sulphur> control. The obtained results are similar to those reported (Hussain et al, 2001;Antar et al, 2008;Abdel-Fattah et al, 2016;Bayoumy et al, 2019).…”
Section: Soil Amendments and Soil Physical Propertiessupporting
confidence: 92%
See 4 more Smart Citations
“…So, the effect different treatments on soil bulk density followed the ascending order such as: compost > gypsum > zeolite > magnetite >Sulphur> control. The obtained results are similar to those reported (Hussain et al, 2001;Antar et al, 2008;Abdel-Fattah et al, 2016;Bayoumy et al, 2019).…”
Section: Soil Amendments and Soil Physical Propertiessupporting
confidence: 92%
“…The effect of application on salinesodic soil reclamation have shown that the soil receiving gypsum at higher rate removes the greatest amount of Na+ from the soil columns and causes a substantial decrease in soil electrical conductivity (EC) and sodium adsorption ratio (SAR). The obtained results seem to agree with Abdel-Fattah et al 2012, Amer and Hashem (2018) and Bayoumy et al (2019).…”
Section: Soil Basic Infiltration Rate (Ir)supporting
confidence: 91%
See 3 more Smart Citations